2017
DOI: 10.1016/j.jsat.2017.01.002
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneity in pathways to abstinence among women in treatment for alcohol use disorder

Abstract: Background Although many providers recommend alcohol abstinence as an initial step in the treatment of alcohol use disorders (AUD), there is a scarcity of research on specific behavioral strategies to achieve this step. The current study examined efficacy of a unique abstinence planning intervention for alcohol in a cognitive behavioral therapy (CBT) outpatient protocol. Design 128 women enrolled in a randomized controlled trial of CBT for AUD at a university-based clinic comprised the sample. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We included 24 original studies, with findings reported in 63 publications (Anton, Moak, Latham, et al, 2005;Anton, Moak, Waid, et al, 1999;Anton, O'Malley, et al, 2006;Babor, 1997;Baros, Latham, and Anton, 2008;Brown et al, 2007;Capone et al, 2011;Carroll et al, 1998;Cisler et al, 1998;Crouch, DiClemente, and Pitts, 2015;Cutler and Fishbain, 2005;Davis et al, 2002;DiClemente, 2011;Donovan et al, 2002;Dundon et al, 2008;Fals-Stewart and Birchler, 2002;Fals-Stewart, Birchler, and Kelley, 2006;Fals-Stewart, O'Farrell, and Lam, 2009;Friedmann et al, 2013;Friend and Pagano, 2007;Gamble et al, 2010;Gastfriend and the COMBINE Study Research Group, 2003;Greenfield et al, 2010;Hallgren, McCrady, and Epstein, 2016;Hallgren, Owens, et al, 2015;Holder et al, 2000;Holzhauer et al, 2017;Ilgen and Moos, 2005;Kelly and Hoeppner, 2013;Litt, Kadden, and Tennen, 2015;Lynch et al, 2010;Magura, Cleland, and Tonigan, 2013;Manuel, Houck, and Moyers, 2012;McCrady, Epstein, Cook, et al, 2009;McCrady, Epstein, Hallgren, et al, 2016;McCrady...…”
Section: Results Of the Searchmentioning
confidence: 99%
“…We included 24 original studies, with findings reported in 63 publications (Anton, Moak, Latham, et al, 2005;Anton, Moak, Waid, et al, 1999;Anton, O'Malley, et al, 2006;Babor, 1997;Baros, Latham, and Anton, 2008;Brown et al, 2007;Capone et al, 2011;Carroll et al, 1998;Cisler et al, 1998;Crouch, DiClemente, and Pitts, 2015;Cutler and Fishbain, 2005;Davis et al, 2002;DiClemente, 2011;Donovan et al, 2002;Dundon et al, 2008;Fals-Stewart and Birchler, 2002;Fals-Stewart, Birchler, and Kelley, 2006;Fals-Stewart, O'Farrell, and Lam, 2009;Friedmann et al, 2013;Friend and Pagano, 2007;Gamble et al, 2010;Gastfriend and the COMBINE Study Research Group, 2003;Greenfield et al, 2010;Hallgren, McCrady, and Epstein, 2016;Hallgren, Owens, et al, 2015;Holder et al, 2000;Holzhauer et al, 2017;Ilgen and Moos, 2005;Kelly and Hoeppner, 2013;Litt, Kadden, and Tennen, 2015;Lynch et al, 2010;Magura, Cleland, and Tonigan, 2013;Manuel, Houck, and Moyers, 2012;McCrady, Epstein, Cook, et al, 2009;McCrady, Epstein, Hallgren, et al, 2016;McCrady...…”
Section: Results Of the Searchmentioning
confidence: 99%
“…This suggests that personalized medicine methods should include assessments of the relieving and rewarding effects of alcohol. Other work uses complex methods such as factor mixture models and network analyses to identify individual characteristics which may moderate the effects of AUD treatment (Holzhauer et al, 2017(Holzhauer et al, , 2020 suggesting specific baseline characteristics which should be included in predictive models and also suggesting that multiway interactions are likely. This suggests that the method used for obtaining predictions with these variables should allow for those interactions.…”
Section: Personalized Medicinementioning
confidence: 99%